Uncovering the Atomistic Mechanism for Calcite Step Growth. - De La Pierre, Marco; Raiteri, Paolo; Stack, A.; Gale, Julian (Wiley VCH, 2017)
Determining a complete atomic-level picture of how minerals grow from aqueous solution remains a challenge as macroscopic rates can be a convolution of many reactions. For the case of calcite (CaCO3 ) in water, computer simulations have been used to map the complex thermodynamic landscape leading to growth of the two distinct steps, acute and obtuse, on the basal surface. The carbonate ion is found to preferentially adsorb at the upper edge of acute steps while Ca(2+) only adsorbs after CO3(2-) . In contrast to the conventional picture, ion pairs prefer to bind at the upper edge of the step with only one ion, at most, coordinated to the step and lower terrace. Migration of the first carbonate ion to a growth site is found to be rate-limiting for kink nucleation, with this process having a lower activation energy on the obtuse step.